Binding Power of Dispute Board Judgment in Construction Dispute Settlement - Yudhantaka, Lintang; Simamora, Yohanes Sogar; Ghansham Anand (Yuridika, 2023)
Construction work in its implementation is carried out based on a contract. If there are problems in carrying out construction work, a dispute between the parties, in this case the service user and the service provider, will occur. Indonesia Law No. 2/2017 about Construction Services (hereafter called UU 2/2017) provides a new dispute resolution model option if problems occur in the construction sector, namely through the Dispute Board. The Dispute Board was created by the International Federation of Consulting Engineers / Federation Internationale des Ingenieurs-Conseils or FIDIC which was adopted into UU 2/2017. However, the regulation regarding the Dispute Board in UU 2/2017 needs to be studied further, especially regarding the nature of the final binding decision, because it still raises problems in its implementation. The purpose of this study is to examine the development of dispute resolution in the field of construction and the implementation of the final and binding nature of dispute board decisions. This study employed legal research methods with a conceptual and statute approach. The results of this study found that construction disputes can be resolved through litigation or non-litigation. The presence of the Dispute Board still does not provide legal certainty for the parties because the nature of the decision is final and binding but is not supported by an implementation mechanism.